This is internet (Townson, Md. : ALA Video/Library Video Network, 1994)
This video explains the Internet in concise, no-nonsense terms. It finds out who uses it and what they use it for, what benefits come from using the Internet and hints for using it more effectively
Keywords: Internet (Computer network)